MANAGEMENT OF SECOND DEGREE UTEROVAGINAL PROLAPSE - Begum, Iqbal; Jadoon, Naila (Journal of Ayub Medical College Abbottabad, 1998)
Uterovaginal prolapse, though not a life threatening disease, can greatly affect the quality of majority of women especially during their menopausal period. Hysterectomy, vaginal or abdominal is usually the treatment of choice. Lefort’s operation is sometimes advocated for severe prolapse in elderly women and for vaginal inversion after hysterectomy.1 It can also be performed under local anaesthesia if needed. Key Words: Second degree uterovaginal prolapse, Lefort’s operation.